IMPLEMENTASI PEMBELAJARAN IPA BERDIFERENSIASI DENGAN MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SMP DI KEDIRI - Fanani, M. Zainal; Erman; Sulastri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the implementation of differentiated learning using the PBL model and increase the cognitive learning scores of class VII A students at SMP Negeri 1 Grogol Kediri. Quantitative research methods were used in this research with a classroom action research (PTK) approach system which was carried out in 2 cycles where each cycle had 4 levels, including planning, implementation, observation and reflection. The data collection process is carried out through a Posttest at the end of each learning cycle. The results of this research show that the average value of cognitive learning outcomes has increased from 72.94 in the pre-cycle stage to 78.84 in cycle 1, and then to 87.64 in cycle 2. The percentage value of learning completeness has also increased, increasing from 64.7% in the pre-cycle stage to 85.5% in cycle 1 and then to 94.1% in cycle 2. Conclusions from the detailed action assessment (PTK) in class VII A students at SMP Negeri 1 Grogol who applied the PBL model with a Differentiated shows an increase in cognitive scores and the percentage of student learning completeness.